2009
DOI: 10.1088/0957-4484/20/13/135603
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation-induced phase transformations in silicon at elevated temperatures

Abstract: The nanoindentation-induced phase transformation behavior of silicon at elevated temperatures (25-150 degrees C) has been studied. Nucleation of Si-III/Si-XII on unloading is enhanced with increasing temperature and at the highest temperatures in an amorphous Si matrix, occurs in a continuous fashion without a pop-out event. Interestingly, for slow unloading at the highest temperatures, formation of Si-III/Si-XII in a crystalline Si matrix was not observed. Elevated temperatures enhance the nucleation of Si-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 22 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…Whereas phase transformations occurred over this whole temperature range, they tentatively proposed a tetragonal form of Si on unloading and subsequent annealing for indentation at 135°C and suggested that this originated from a new unidentifiable phase formed at 135°C. Furthermore, Ruffell et al (2009b) performed similar studies in the 25-150°C temperature range on dc-Si and found only the expected r8/bc8 or a-Si end phases. However, the probability of formation of the bc8/r8 end phase (as opposed to an a-Si end phase) was enhanced with increasing temperature during fast unloading.…”
Section: Temperature-dependent Studiesmentioning
confidence: 80%
See 1 more Smart Citation
“…Whereas phase transformations occurred over this whole temperature range, they tentatively proposed a tetragonal form of Si on unloading and subsequent annealing for indentation at 135°C and suggested that this originated from a new unidentifiable phase formed at 135°C. Furthermore, Ruffell et al (2009b) performed similar studies in the 25-150°C temperature range on dc-Si and found only the expected r8/bc8 or a-Si end phases. However, the probability of formation of the bc8/r8 end phase (as opposed to an a-Si end phase) was enhanced with increasing temperature during fast unloading.…”
Section: Temperature-dependent Studiesmentioning
confidence: 80%
“…5, we plot some very recent results of Kiran et al (2015) who have improved and extended the elevated temperature indentation work of Ruffell et al (2009b). Figure 5 shows that the probability of an r8/bc8 end phase increases up to 150°C.…”
Section: Temperature-dependent Studiesmentioning
confidence: 98%
“…Research on single crystal silicon under external loads has been given much attention [1,2,3,4,5]. Nanoindentation as a powerful method to characterize properties of materials in micro/nano scale also has been used to study mechanical response of single crystal silicon under the penetration load [6,7,8,9,10,11,12,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Unlike general materials which have smooth load-depth curves, discontinuities in the unloading curves named pop-out and elbow were observed during indentation testing of single crystal silicon [7,10,12,13,14,15,16], which responded to phase transformations of silicon beneath the indenter. Results of Raman microspectroscopy analysis of nanoindentations indicate that pop-out corresponds to the formation of Si–XII and Si–III phases [17], and elbow resulted from the amorphization of silicon on pressure release [13,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation